Pengaruh Sales Growth Dan Transfer Pricing Terhadap Tax Avoidance - Wongsosudono, Corinna; Wati, Widya; Riyan, Rifdah Dara; Siregar, Hasrul; Pardede, Sovia Lolita Apriani; Faridani, Mutia Riska (Universitas Islam Islam Sumatera Utara, 2023)
This research aims to determine the effect of tax avoidance. The variables tested in this research are sales growth and transfer pricing as independent variables. The dependent variable used is tax avoidance. The population used in this research is 72 food and beverage companies listed on the Indonesia Stock Exchange 2018-2021. The sample in this research was 9 companies selected based on the purposive sampling method. The data analysis technique used was multiple linear regression analysis. The results of this research show that partial sales growth has a positive effect. Transfer pricing partially has a negative effect. The research conclusion is that simultaneously sales growth and transfer pricing influence tax avoidance.